2002
DOI: 10.1002/ppul.10140
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood lymphopenia and neutrophilia in children with severe respiratory syncytial virus disease

Abstract: It is not known why respiratory syncytial virus (RSV) is associated with prolonged sequelae in many children. Measles virus (also a paramyxovirus), acute stress in sepsis, and cardiac bypass all cause lymphopenia. Using a retrospective analysis of records of children in Bristol with RSV infections over 5 years, we found that children with RSV had lower lymphocyte counts than unstressed, stable children prior to cardiac surgery. Children who required intensive care had the lowest lymphocyte counts. Neutrophil c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 17 publications
5
58
0
Order By: Relevance
“…We cannot exclude other, DC-independent, explanations that may contribute to the weak primary T cell response to CVB, and for the diminished LCMV-specific T cell response in wtCVB3-infected mice. For example, somewhat counter-intuitively, many viruses cause a rapid but transient lymphopenia (Bautista et al , 2003; Díaz-San Segundo et al , 2006; Dietz, Jr. et al , 1979; Geisbert et al , 2000; Grubman et al , 2008; Nfon et al , 2010; O'Donnell and Carrington, 2002; Okada et al , 2000; Peacock et al , 2003); the effect, which is mediated by interferons (Kamphuis et al , 2006; Schattner et al , 1983), has been shown to occur during enteroviral infections (Bautista et al , 2003; Nfon et al , 2010) and we have observed it in mice infected with wtCVB3 (Althof & Whitton, unpublished).…”
Section: Discussionmentioning
confidence: 83%
“…We cannot exclude other, DC-independent, explanations that may contribute to the weak primary T cell response to CVB, and for the diminished LCMV-specific T cell response in wtCVB3-infected mice. For example, somewhat counter-intuitively, many viruses cause a rapid but transient lymphopenia (Bautista et al , 2003; Díaz-San Segundo et al , 2006; Dietz, Jr. et al , 1979; Geisbert et al , 2000; Grubman et al , 2008; Nfon et al , 2010; O'Donnell and Carrington, 2002; Okada et al , 2000; Peacock et al , 2003); the effect, which is mediated by interferons (Kamphuis et al , 2006; Schattner et al , 1983), has been shown to occur during enteroviral infections (Bautista et al , 2003; Nfon et al , 2010) and we have observed it in mice infected with wtCVB3 (Althof & Whitton, unpublished).…”
Section: Discussionmentioning
confidence: 83%
“…The lack of regulation of the NK system, mediated by a poor expression of CD94-NKG2 receptors could lead to increased of lung damage, either through increased direct RSV damage on epithelial cells in the absence of an effective immune response or through apoptotic signals in the lung 20,60 or in blood. 32,37 Finally, the development of wheezing during one year of follow-up had no relation to these immunologic markers studied during the first days of acute infection. The mechanisms by which avian viruses cross species barriers to infect humans or other mammals, either causing dead-end infections or leading to subsequent human-to-human transmission, are unknown.…”
Section: Discussionmentioning
confidence: 89%
“…The increase in mucus-positive cells after RSV infection may be the result of increased recruitment of neutrophils to the lung. Neutrophils are the predominant leukocytes in the airways of infants with RSV-induced bronchiolitis (14,31,41), and recruitment into the lungs can contribute to mucus production through release of neutrophil elastase (1,23). Both smoke-exposed and air-exposed mice had a significant increase in neutrophil numbers 4 and 7 days after secondary RSV infection compared with VEH controls.…”
Section: Discussionmentioning
confidence: 99%